PEMBERLAKUAN TARIF CUKAI ALKOHOL SPESIFIK DALAM PERSPEKTIF HUKUM BISNIS DI KOTA JAMBI - Abdul Hariss (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Among the products that are withdrawn excise goods are goods products using raw materials alcohol ranging from 1% (one percent) to above 20% (twenty percent), such as beer and other beverages. While determining the amount of excise duty of a good product that contains alcohol is based on the provisions of the applicable law governing alcohol rates.Determination of alcohol excise rates there are direct from central government officials and some are issued by local government officials (local laws).In the city of Jambi was no withdrawal of excise duty on companies which produce beverages containing alcohol that is at PT. Relieved Heart, where the product affected by the withdrawal rates beverage alcohol is a beverage brand Cap Tigers.Due to the tax rates related to the results of trading products, the indirect tax rates included in the business law sectionKeyword :  alcohol, business law